Measuring and allocating systemic risk - Markus Konrad Brunnermeier; Patrick Cheridito (Risks, 2019)
In this paper, we develop a framework for measuring, allocating and managing systemic risk. SystRisk, our measure of total systemic risk, captures the a priori cost to society for providing tail-risk insurance to the financial system. Our allocation principle distributes the total systemic risk among individual institutions according to their size-shifted marginal contributions. To describe economic shocks and systemic feedback effects, we propose a reduced form stochastic model that can be calibrated to historical data. We also discuss systemic risk limits, systemic risk charges and a cap and trade system for systemic risk.
Keywords: 330; systemic risk measure; systemic risk allocation; feedback effects; shadow prices; systemic risk limits; systemic risk charges; cap and trade